Reading, experience, and learning: pedagogical contributions from Bachelard’s Intuition of the Instant - Juliao, Carlos Germán (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article raises the relation between reading, experience, and learning, based on the exercise of learning reading that Bachelard performs in his text The Intuition of the Instant, about the book Siloë, by Roupnel, where his ideas about time and duration that came from his academic training and the reading of Bergson's work are confronted. The problematization in learning is addressed, as well as the pedagogy of demonstrating and imagining. It is confirmed that one learns against prior knowledge, deconstructing incorrect knowledge, and overcoming mental obstacles. Following Bachelard's experience, the possibility of a pedagogy centered on the recovery of the precise moment of learning is raised, rethinking everything that an orthodox conception of the didactic task leaves out, without taking advantage of the hermeneutical richness of the learning process.